Caminhos e Descaminhos: a Pesquisa na Formação de Professores de Língua Estrangeira - Gimenez, Telma (The ESPecialist, 2012)
This article reports the experience of a group of teachers working with EFL Teaching Methodology and Practice at the undergraduate level in a state university in the south of Brazil. The article is divided into four parts: destinations, compasses and maps, paths and crossroads. Destinations, compasses and maps provide the theoretical background with a brief review of literature in the area of EFL education and research methodology in action research. Paths and crossroads aim at providing reflections on the group’s experience in incorporating a research perspective into the preparation of prospective EFL teachers at the University level.